One Developmental Model, Two Developmental Stages: Supervisees' Experiences of the Developmental Comprehensive Supervision Model - Eryilmaz, Ali; Bektas-Aydin, Ceren (SPRINGER, 2022)
In this study, a supervision model developed by considering the needs of counselor education in Turkey was evaluated. As part of the study, 11 undergraduate and 7 master's counseling and guidance students were supervised with the Developmental Comprehensive Supervision Model. The in-depth experiences of supervisees regarding the model were explored. Thematic analysis method was used for the data analysis. Two themes were identified in the undergraduate group: supervision process and outcome. Four themes were identified in the graduate group: supervision process, outcome, supervisor characteristics, and disadvantages. The results were discussed in the context of developmental supervision theory.
Keywords: Supervision; Supervisee; Developmental supervision model; Counselor education; Self-regulated learning; CLINICAL SUPERVISION; COUNSELORS; THERAPISTS; Psychology